The Role of Work Environment in Training Sustainment: A Meta-Analysis. (February 2020) - Hughes, Ashley M.; Zajac, Stephanie; Woods, Amanda L.; Salas, Eduardo
Objective: The purpose of this meta-analytic review is to examine the role of three work environment support variables (i.e., peer, supervisor, and organizational support) in training transfer and sustainment or long-term use of learned knowledge, skills, and attitudes (KSAs). Background: Estimates demonstrate that little training is transferred to the job, wasting billions in organizational spending each year and resulting in significant loss to safety and individual and team performance. Prior research shows the importance of a supportive work environment to facilitating transfer; however, we know little of the relative importance of specific support variables. This study seeks to examine the unique roles of distinct support variables in training transfer. Method: A meta-analysis was conducted with multiple regressions to answer three primary research questions. Results: All work environment support variables demonstrate moderate and positive correlations with transfer of training. Furthermore, multiple regressions demonstrate that each factor of the work environment explains unique variance as a predictor, with the model accounting for 32% of transfer and peer support accounting for most of R 2 . Motivation to transfer mediates the relationship between all three work environment support variables and transfer. Furthermore, three support variables are positively related to sustainment, with peer and supervisor support showing the strongest relationships. Conclusion: Findings illuminate the relative contribution of peer, supervisor, and organizational support to transfer and sustainment of training. As transfer continues to be an important yet understudied measure of the effectiveness of workplace training, these findings hold implications for both research and practice.